The new constitutional hermeneutics and the discriction of judicial decisions in concreteing fundamental rights (Revista Direito em Debate, 2022)
The decadence of legalism from legal positivism caused the advent of legal post-positivism, proposing normative force to legal principles, giving rise to the emergence of neoconstitutionalism, in view of the need to guarantee the effective realization of fundamental rights. In view of this, a new constitutional Hermeneutics originates. These phenomena, therefore, empower the Judiciary and intensify judicial discretion. Thus, the objective of the present investigation is to analyze how the use of New Hermeneutics can cause excessively discretionary judicial decisions. Therefore, using the deductive method, through a bibliographic survey, it was performed a review of the doctrinal literature, looking at the historicity of the legal phenomenon mentioned until the advent of neoconstitutionalism and the emergence of a New Constitutional Hermeneutics within this new jusfilosofico paradigm. Then, the maxim of proportionality of Robert Alexy is analyzed as one of the interpretative methods originating from neoconstitutionalism, later demonstrating that the discretionary use of principlist hermeneutics is propitiated by a failure in the application of the weighting theory, which provides the judge the free will to judge and also as a result of a misapplication of the maxim of proportionality by the Brazilian judiciary. Finally, it appears that Dworkin's Theory and the Critical Theory of Lênio Streck, based on Philosophical Hermeneutics and on the integrity of Ronald Dworkin, are shown as possible solutions to the problem that presents itself, in order to overcome the discretion in the materialization fundamental rights.Keywords: Philosophical Hermeneutics; Neoconstitutionalism; Discretion.